HOW DO STUDENTS LEARN WRITING EASILY - Janah, Miftahul; Tristiana, Novita Eka (JURNAL SMART, 2019)
This CAR intends to improve students’ writing ability. The data were collected through questionnaire, observation, and documents. Assembling the data, coding the data, comparing the data, building meanings and interpretations, and  reporting the outcomes were the steps to analyze the data. The result showed that there was improvement on stdents’ writing ability, that was in cycle 1, the mean score was 63.28, and  70.97 in cycle 2.  The questionnaire data was also showed that 47% students strongly agreed and 33% of them agreed that Collaborative Writing Technique could encourage them to write and help them to improve their writing ability.